2019
DOI: 10.1016/j.jot.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Early osteointegration evaluation of porous Ti6Al4V scaffolds designed based on triply periodic minimal surface models

Abstract: BackgroundThe graded porous structures were designed using triply periodic minimal surfaces models to mimic the biomechanical properties of bone. The mechanical properties and bone formation ability were evaluated to explore the feasibility of the design method in bone tissue engineering.MethodsThe scaffolds were designed using a P-surface with different pore sizes. All materials were fabricated using 3D printing technology and the mechanical properties were tested by an electronic universal testing device. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…In a recent in vivo study, Schwarz-based porous graded titanium alloy scaffolds produced by SLM demonstrated good osteointegration in tibial defects in mini pigs, highlighting the promising features of this particular TPMS structure. 63 Overall, these results suggest that multimodal pore size distributions may have a higher interference in cell fate when interconnectivity is guaranteed.…”
Section: Discussionmentioning
confidence: 85%
“…In a recent in vivo study, Schwarz-based porous graded titanium alloy scaffolds produced by SLM demonstrated good osteointegration in tibial defects in mini pigs, highlighting the promising features of this particular TPMS structure. 63 Overall, these results suggest that multimodal pore size distributions may have a higher interference in cell fate when interconnectivity is guaranteed.…”
Section: Discussionmentioning
confidence: 85%
“…The matching degree of titanium implants with the host bone is also higher, and the incidence of bone resorption and implant loosening is also reduced [ 3 ]. Porous structures are considered to be an effective method to eliminate elastic modulus mismatches [ 4 – 6 ]. Porous titanium scaffolds with a low elastic modulus can further reduce the stress masking effect, fit well with the host bone, reduce bone absorption, and promote rapid bone formation and integration at the bone-implant interface [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ali et al [13] designed eight different bone scaffolds based on TPMS and proved these architectures have a significant impact on permeability. Li et al [14] successfully prepared the Ti6Al4V scaffold with TPMS of p-cell. With the least surface area, better fluid permeability [14][15][16][17] and improved early osteogenesis, osteointegration resulted from the decreased stress shielding effect [14] were achieved with the p-cell TPMS structure.…”
Section: Introduction mentioning
confidence: 99%
“…Li et al [14] successfully prepared the Ti6Al4V scaffold with TPMS of p-cell. With the least surface area, better fluid permeability [14][15][16][17] and improved early osteogenesis, osteointegration resulted from the decreased stress shielding effect [14] were achieved with the p-cell TPMS structure. However, there is still no HA bioceramics with such a bio-inspired TPMS structure being studied.…”
Section: Introduction mentioning
confidence: 99%